Empirical Study of Leading Products in the Sidoarjo Region - Setyawan, Dendy; Ujianto, Ujianto; Andjarwati, Tri (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Sidoarjo as a government area in East Java has its own uniqueness because it is a mixed area which is basically a district government but has several sub-district cities, even one of which has a fairly large size and can be said to be an independent city. In addition, it also has a variety of natural resources and artificial products that can be considered localized, which each ones can become a featured product. This descriptive research was conducted using an empirical literature study method, where researchers searched -both on Google.com and Google Scholar- for various studies using intentional keywords. 16 qualitative studies and 2 quantitative studies were studied. The result shows that the condition of superior products in Sidoarjo has quite a lot of problems that make superior products have no added value and have low competitiveness. However, the current value and competitiveness of featured products cannot be imagined because these studies examine the quality of superior products against competitors.